Dampak aplikasi kumatetralil dan Sarcocystis singaporensis terhadap serangan hama tikus di perkebunan kelapa sawit - Mahardika Gama Pradana; Hari Priwiratama; Agus Eko Prasetyo; Agus Susanto (Jurnal Penelitian Kelapa Sawit, 2021)
The management of rat attack in oil palm plantation is commonly achieved through rodenticide application as well as in combination with the utilization of natural enemies. In this study, field efficacy of two rodenticide active ingredients i.e. coumatetralyl and Sarcocystis singaporensis against Rattus tiomanicus was conducted in mature oil palm blocks. The experiment was carried out in a randomized complete block design consisting of 3 treatments and 6 blocks/replicates. The application of coumatetralyl was conducted at the dose of 1 block bait per palm, while S. singaporensis treatment was conducted at the dose of 2 pellets per palm. The rodenticide application was carried out four times at five days interval. The result showed that incidence of rat attack decreased in all experimental blocks. The incidence of rat attack on coumatetralyl treatment was significantly lower than the control block at 5 and 10 days after application (daa), where as S. singaporensis treatment only showed a significant reduction at 5 daa. The average rate of reduction in rat attack during application of coumatetralyl, S. singaporensis, and control treatments was 53.80%; 38.58%; and 21.86%, respectively. The intensity of rat attack on male flowers before application was ranged between 31.87% to 40.64%, while the intensity on fruit bunches was ranged from 4.85% - 7.52%. The decrease in the incidence and intensity of rat attack is in line with the decrease in rodenticide consumption. In coumatetralyl treatment, consumed bait decreased from 75.02% to 57.03%, while in S. singaporensis treatment it decreased from 61.38% to 47.20%. In general, the efficacy value of coumatetralyl was higher than that of S. singaporensis.